Indolenine-Based Derivatives as Customizable Two-Photon Fluorescent Probes for pH Bioimaging in Living Cells - Benítez-Martín, Carlos; Guadix-Domínguez, Juan Antonio; Pearson, John; Nájera-Albendín, Francisco; Pérez-Pomares, José María; Perez-Inestrosa, Ezequiel (American Chemical Society, 2020)
Novel pH probes based on 2-(6-methoxynaphthalen-2-yl)-3,3-dimethyl3H-indole have been synthesized and characterized. These compounds display excellent “off−on” fluorescence responses to acidic pH especially under two-photon (TP) excitation conditions as well as strong selectivity and sensitivity toward H+ . These features are supported by fluorescence quantum yields over 35%, TP cross sections ∼60 GM, and good resistance to photodegradation under acidic conditions. The synthetic versatility of this model allows subcellular targets to be tuned through minor scaffold modifications without affecting its optical characteristics. The effectiveness of the probes’ innate photophysical properties and the structural modifications for different pH-related applications are demonstrated in mouse embryonic fibroblast cells
Keywords: Detectores de fotones; Intracellular pH; pH sensor; Two-photon absorption; Fluorescent probe; Biosensor